1997
DOI: 10.2166/wst.1997.0749
|View full text |Cite
|
Sign up to set email alerts
|

Survival of legionella pneumophila and salmonella typhimurium in biofilm systems

Abstract: Biofilms are found in many water supply systems where they form an environment in which different bacteria can be entrapped for long periods. Besides the aesthetic aspect, biofilm has a major contribution in biocorrosion, disinfection inefficiency and possibly may act as a reservoir for pathogenic and non-pathogenic microorganisms. In the present study, two pathogenic bacteria Legionella pneumophila and Salmonella typhimurium WG-49 were introduced into a biofilm simulation flow system supplied with sterile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…Bacterial biofilms developing in distribution systems receiving chlorinated water have been repeatedly reported by previous investigators (LeChevallier et al, 1987(LeChevallier et al, , 1988(LeChevallier et al, , 1990Van der Wende and Characklis, 1990; Camper et al, , 1998,1999, 2000, 2002). Although the present investigation did not deal with the identification of various pathogenic and opportunistic pathogens, the survival and multiplication of heterotrophic bacteria such as Escherichia coli, Pseudomonas, Aeromonas, Klebsiella, Legionella spp., Mycobacterium, Campylobacter, Salmonella typhimurium and Helicobacter pylori have been observed within biofilms occurring in potable water systems with standard chlorine residual concentrations (Engel et al, 1980;Wadowsky et al, 1982;Burke et al, 1984;Armon et al, 1997;Mackey et al, 1998;Camper et al,1999;Momba et al, 1999). The capability of E. coli to survive a high free chlorine residual dose of 0.7 mg·l -1 and to attach on pipe materials such as stainless steels was reported by Momba and coworkers in 1999.…”
Section: Discussionmentioning
confidence: 89%
“…Bacterial biofilms developing in distribution systems receiving chlorinated water have been repeatedly reported by previous investigators (LeChevallier et al, 1987(LeChevallier et al, , 1988(LeChevallier et al, , 1990Van der Wende and Characklis, 1990; Camper et al, , 1998,1999, 2000, 2002). Although the present investigation did not deal with the identification of various pathogenic and opportunistic pathogens, the survival and multiplication of heterotrophic bacteria such as Escherichia coli, Pseudomonas, Aeromonas, Klebsiella, Legionella spp., Mycobacterium, Campylobacter, Salmonella typhimurium and Helicobacter pylori have been observed within biofilms occurring in potable water systems with standard chlorine residual concentrations (Engel et al, 1980;Wadowsky et al, 1982;Burke et al, 1984;Armon et al, 1997;Mackey et al, 1998;Camper et al,1999;Momba et al, 1999). The capability of E. coli to survive a high free chlorine residual dose of 0.7 mg·l -1 and to attach on pipe materials such as stainless steels was reported by Momba and coworkers in 1999.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies at the lab scale have demonstrated that even in the presence of detectable levels of chlorine, E. coli can be incorporated in biofilms (34), survive in the biofilm for up to 40 days (1,17), and persist there in a metabolically active form (13,40). Some authors suggest that E. coli can even grow in drinking water distribution systems (7) because these bacteria can adapt to the oligotrophic environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that bacteria attached to surfaces show greater resistance to disinfection (15,19,20,36). Biofilms in distribution systems may provide a favorable condition for some bacteria, such as opportunistic pathogens (e.g., Legionella spp., Pseudomonas aeruginosa, and Mycobacterium avium), to colonize it and may harbor pathogens, such as Salmonella enterica serovar Typhimurium, which have entered the distribution system (1,5,18,28). It has been shown in lab-scale experiments that E. coli can survive in biofilters (24) and even multiply in the biofilm (17,34,40), which again raises the question of its suitability as a drinking water quality indicator.…”
mentioning
confidence: 99%
“…Multiple studies have shown that Legionella pneumophila can persist in or on simulated drinking water biofilm (3,11,19,26,36), as can Helicobacter pylori, but the results are limited (23,28). Virus persistence has also been demonstrated, but published results have been variable (19,29,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, information on persistence of microbiological agents in water distribution system pipe material is limited. Research available in the open literature mostly focuses on bacteria, including coliforms (7,12,25,37), Helicobacter pylori (23, 28), Legionella pneumophila (3,11,19,26,36), Aeromonas hydrophila (5), and Salmonella enterica serovar Typhimurium (3). Other researchers have investigated the persistence of injected viruses (19,29,35) as well as wastewater cross-connections with drinking water pipes (13, 24).…”
mentioning
confidence: 99%